Legal Protection For Medical Traditional Treatment Based On Empirical The Government Act No. 103/2014 On Traditional Health Services In The District Semarang - Erny Amperawati; Hermawan Pancasiwi; Hari Pudjo Nugroho (SOEPRA, 2018)
The purpose of this study was to know and understand the provisions of legal protection for medical traditional treatment the empirical basis of Law and Act Government No. 103/2014; authority of the local government of Semarang Regency in applying the legal protection aspect for the health of traditional medicine; and health strategies in Semarang Regency in integrating traditional medicine with standardization of health services in accordance with applicable Laws and Regulations.Research this use method qualitative with approach juridical sociological. Specification from research this is research descriptive. Method analysis of data on research this use qualitative data analysis.The results of this study are: (1) Interest use treatment Traditionally, not also inseparable from the increase complexity illness society, of accompanied with needs cost further treatment Great. As a result, treatment traditional back ogled as wrong one alternative problem solving. Supported with ingredients raw nature provided, as well as existence knowledge hereditary from system treatment Traditionally, the interest community will utilization treatment traditional permanent there is and increasingly increased; (2) The authority government inprotection law service health traditional could reviewed from function government based on protection on law. There is three kind of form protection law government that is as maker legislation, implementing Constitution and as supervisor legislation. As maker legislation, overnment authorized make something regulations governing with concrete about service health traditional. Health Law set field health onthorough but no Specific in set service health traditional. Setting more special arranged in PP 103/2014 as regulations implementing the Health Law; and (3) Services Health Traditional in run activities with aim for treat or cure person pain, close possibility for looking for benefit economical anyway. So on general provider services service health traditional could it says as perpetrators businesses engaged in field service-services health, namely service health traditional. This corresponding with definition perpetrators business in Article 1 paragraph 3 of Law  Protection Consumers meaningful wide. Understanding perpetrators significant effort large the will make it easy consumer in demanding replace loss when there problems law. Rules Government No. 103/2014 only give permission on two expertise only on healthier treatment traditional Empirical